Parainfluenza and corona viruses in a fallow deer (Dama dama) with fatal respiratory disease - Dastjerdi, Akbar; Floyd, Tobias; Swinson, Vanessa; Davies, Hannah; Barber, Andrew; Wight, Alan (Frontiers in Veterinary Science, 2022)
Parainfluenza virus type 3 (PIV-3) and coronaviruses (CoV) are commonly found in respiratory tracts of ruminants and capable of causing clinical disease. Here, we investigated the cause of ill-thrift and sudden death in a five-month-old male fallow deer which occurred in December 2019. The calf was one of the five calves in a herd of 170 deer that, along with three adult hinds, died during a 2-week period. The deer calves were in a shed, sharing airspace with young cattle that had been reported to be coughing. Significant gross pathology was observed in the respiratory and alimentary tracts of the deer calf and histopathology of the lung and trachea was suggestive of likely involvement of PIV-3. Strong and specific cytoplasmic labelling of bronchiolar epithelium and terminal airway, alike those seen with PIV-3 pneumonia in cattle, was observed using a polyclonal bovine PIV-3 antibody. Metagenomic analysis detected a PIV-3 and a CoV in the lung tissue. The PIV-3 L protein gene had the highest sequence identity with those of bovine PIV-3 (83.1 to 98.4%) and phylogenetically clustered with bovine PIV-3 in the genotype C. The CoV spike protein gene shared 96.7% to 97.9% sequence identity with those of bovine CoVs, but only 53.1% identity with SARS-CoV-2 reference virus. We believe this is the first report of PIV-3 and CoV co-infection in fallow deer and their association with fatal pneumonia; major pathology caused by PIV-3.